Investigating South Africa' foreign policy towards the SADC region : the case study of the Democratic Republic of Congo, 2009-2018 - Langa, Nduduzo (My University, 2020)
South Africa’s foreign policy towards the Southern African Development Community (SADC) region, particularly during Thabo Mbeki’s tenure, has received substantial scholarly attention. Similarly, South Africa’s domestic political arena has been a subject of significant scholarly inquiry during Jacob Zuma’s tenure. Understandably, when one considers the domestic scandals that clouded Zuma’s presidency, the foreign policy of the Zuma administration, specifically towards the SADC region, has received underwhelming scholarly attention. Therefore, the present study is a contribution to the limited available studies on the Zuma administration’s foreign policy towards the SADC region. Noting the importance of the DRC in SADC region international relations, the DRC is used as a case study. The DRC’s experience of a seemingly ceaseless or recurrent conflict makes it a suitable case for the assessment of the Zuma administration’s foreign policy. This is because it would be difficult for a South Africa that is largely viewed as the SADC region’s regional leader to remain indifferent while a fellow SADC member state experiences continuous instability. To achieve its objectives, the study employed document review as a data collection method. The study found that South Africa under Zuma prioritised economic diplomacy. As such, it actively participated in the neutralisation, through military means, of rebel groups in the DRC. It would not be farfetched to submit that this was an attempt to create an environment that is more conducive to economic activity in the DRC so as to improve economic relations between the two countries. Keywords: South Africa, SADC, Foreign Policy, Democratic Republic of Congo, Zuma, Afrocentricity, Southern Africa.
Thesis (M. A. (International Politics)) -- University of Limpopo, 2020
Keywords: South Africa; SADC; Foreign Policy; Democratic Republic of Congo; Zuma; Afrocentricity; International economic relations; South Africa -- Foreign relations -- 2009-2018